2017
DOI: 10.3168/jds.2016-12318
|View full text |Cite
|
Sign up to set email alerts
|

Short communication: Optimization of a timed artificial insemination program for reproductive management of heifers in Canadian dairy herds

Abstract: Pregnancy per AI (P/AI) following the use of 1 of 2 timed AI (TAI) protocols and 2 different intervals between TAI and resynchronization were compared in heifers that were inseminated with either conventional or sex-sorted semen. Holstein heifers (n = 317; 527 inseminations) were submitted to a 5-d Cosynch protocol with (+) or without (-) GnRH at the time of controlled internal drug release (CIDR) insertion on d 0, CIDR removal and a single PGF treatment on d 5, and TAI plus GnRH on d 8 (72 h later). Visual es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
5

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 16 publications
0
12
0
5
Order By: Relevance
“…En este sentido, Macmillan et al (2017) compararon los protocolos + y -GnRH usando semen convencional o sexado en novillas de leche. Aunque la diferencia no fue estadísticamente significativa, se observó una mayor tasa de preñez en el caso de semen sexado combinado con el protocolo -GnRH en comparación con el protocolo +GnRH (60 vs. 50%, res pec tivamente).…”
Section: Utilización De Semen Sexadounclassified
See 2 more Smart Citations
“…En este sentido, Macmillan et al (2017) compararon los protocolos + y -GnRH usando semen convencional o sexado en novillas de leche. Aunque la diferencia no fue estadísticamente significativa, se observó una mayor tasa de preñez en el caso de semen sexado combinado con el protocolo -GnRH en comparación con el protocolo +GnRH (60 vs. 50%, res pec tivamente).…”
Section: Utilización De Semen Sexadounclassified
“…Por ello, nos hemos planteado la hipótesis de si el uso de una detección corta de celos antes de la IATF para la identifi-cación de animales idóneos para una IA temprana (56-60 horas después de la retirada del CIDR) aumentaría los porcentajes de preñez. En este sentido, Macmillan et al (2017) realizaron una detección de celo a las 36 y 48 horas de la retirada del CIDR. Las novillas que mostraron celo se inseminaron a las 60 horas de la retirada del CIDR, frente a las que no expresaron celo, que se inseminaron a las 72 horas (IATF).…”
Section: Colazo Y Mapletoftunclassified
See 1 more Smart Citation
“…Accordingly, the improvement of the veterinary advisory service and its structured approach to animals whose indicators suggest a reproductive problem arises as one of the primary goals in the dairy sector in BH. Although not commonly used in BH, timed AI can be introduced as an alternative cost-effective Veterinary Medicine International and viable solution for this group of animals, as previously reported [23,24]. Animals with chronic reproductive problems could also be removed from the dairy herd although farmers reported that reproductive culling is not a common management practice in their farms in Una-Sana Canton.…”
Section: Discussionmentioning
confidence: 99%
“…A média geral em todas as novilhas, independentemente do tratamento foi de 76,2%, o que pode ser considerada uma alta taxa de concepção, por se tratar de novilhas que tiveram a lactação induzida. Além disso, esta taxa de concepção é similar àquela descrita para novilhas nulíparas que não foram submetidas a um PIL em outros estudos: 64,2% com novilhas da raça Jersey, 71,8% da raça Holandesa e 70,4% da raça Jersolando (XU; BURTON, 1999), 68% para novilhas da raça Holandesa (MACMILLAN et al, 2017).Estes resultados sugerem que o presente PIL não afetou a performance reprodutiva das novilhas quando comparado ao de nulíparas não induzidas. Resultados inferiores de 54% de taxas de prenhez acumulada após 5 IATFs foram obtidos em nulíparas não submetidas a indução de lactação antes da primeira prenhez (NORMAN et al, 2010).…”
Section: Cistos Folicularese Retorno à Ciclicidadeunclassified